Neurocognitive function in procedures correcting severe aortic valve stenosis: patterns and determinants - Ranucci, L.; Brischigiaro, L.; Mazzotta, V.; Anguissola, M.; Menicanti, L.; Bedogni, F.; Ranucci, M. (Frontiers in Cardiovascular Medicine, 2024)
Background Neurocognitive changes occurring after a surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) procedure for the correction of severe aortic stenosis (AS) have not been widely addressed and, if addressed, have produced conflicting results. The purpose of this study is to identify the pre-procedural neurocognitive pattern and its determinants in a setting of elderly (>65 years) patients with severe AS undergoing SAVR or TAVI and the changes occurring at a 2–3 month follow-up. Methods This was a prospective cohort study included in the Italian Registry on Outcomes in Aortic Stenosis Treatment in Elderly Patients. Patients were assessed both before and after (2–3 months) the procedure using the Montreal Cognitive Assessment (MoCA) test. Data on periprocedural demographics, clinical factors, and outcome measures were collected. Results Before the procedure, 70% of the patients demonstrated a MoCA score <23 points, which was indicative of cognitive dysfunction. The factors associated with neurocognitive dysfunction were age, functional capacity, chronic heart failure, and hemoglobin levels. After the procedure, there was an overall improvement in the MoCA score of the patients, but 28% of the patients showed a reliable worsening of their condition. The factors associated with MoCA worsening were platelet transfusions and the amount of red blood cell units transfused. Conclusion The correction of severe AS leads to an improvement in neurocognitive function after 2–3 months. This improvement does not differentiate between SAVR and TAVI after matching for pre-procedural factors. The only modifiable factor associated with pre-procedural neurocognitive function is anemia, and anemia correction with red blood cell transfusions is associated with a worsening of neurocognitive function. This leads to the hypothesis that anemia correction before the procedure (with iron and/or erythropoietin) may limit the risk of a post-procedural worsening of neurocognitive function.